2020
DOI: 10.1080/13685538.2020.1749996
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between atherogenic indexes and erectile dysfunction

Abstract: Aside from the ordinary plasma lipid level measurements, the ratios based on individual plasma lipid levels such as atherogenic index of plasma (AIP), Castelli's risk index 1/2 (CRI-1/2), and atherogenic coefficient (AC) are the novel parameters to evaluate the patients with a high risk of CVD. In this study, we aim to evaluate the relationship between AIP, AC, and CRI-1/2 with increased risk of ED. Between April 2018 and February 2019, 253 patients, who were diagnosed as a vasculogenic ED in our clinic, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…The results of the research of Culha et al [28] demonstrated that both Castelli's risk index CR-1 (total cholesterol/HDL) and AIP (atherogenic index of plasma) have a positive correlation with the severity of erectile dysfunction. The authors believed that patients with higher CR-1 and AIP values were likely to have a more severe erectile dysfunction in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the research of Culha et al [28] demonstrated that both Castelli's risk index CR-1 (total cholesterol/HDL) and AIP (atherogenic index of plasma) have a positive correlation with the severity of erectile dysfunction. The authors believed that patients with higher CR-1 and AIP values were likely to have a more severe erectile dysfunction in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, it has been observed that these ratios such as CRI-1/2 are more susceptible than the conventional lipid biomarkers in predicting CVD (Culha, Canat, et al, 2020;Kalelioglu et al, 2017;Uslu et al, 2017). Specific ratios of plasma lipid levels have been reported to be significantly stronger predictors than HDL-C or LDL-C plasma levels in predicting CVD risk (Nwagha et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial dysfunction is at the beginning of these mechanisms [13]. A positive correlation between the severity of ED in men with a high atherogenic index has recently been demonstrated [14]. The IIEF-5 test is a well-established method to evaluate ED [9].…”
Section: Discussionmentioning
confidence: 99%